PENGARUH MANFAAT UTILITARIAN, KOMUNIKASI DARI MULUT KE MULUT DAN PERILAKU MENCARI VARIASI TERHADAP PERPINDAHAN MEREK ( STUDI PADA KONSUMEN TEH PUCUK HARUM DI KOTA PONTIANAK) - B1023131064, Rizki Hidayat (Jurnal Manajemen Update, 2017)
This study aimed to determine the influence of utilitarian benefits, word of mouth and variety seeking to brands switching of Teh Pucuk Harum consumers in Pontianak city. Populations in this research are consumers of Teh Pucuk Harum that lived in Pontianak city, with total samples 100 respondens. The samples processed with purposive sampling technique with double linier regression analysis tools. The results of this analysis show that the benefits of utilitarian and variety seeking was significant influenced to Teh Pucuk Harum brand switching, whereas word of mouth was not significantly influenced to Teh Pucuk Harum brand switching. Predictive of capability of three variables in explaining the influenced to brands switching is 38 % while the remaining 62% explained by other factors out of this research model.Â Keyword: Benefits of utilitarian, word of mouth, variety seeking and brands switching.